2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7591887
|View full text |Cite
|
Sign up to set email alerts
|

ImQuant — An image based fluorescence reader for quantitative lateral flow immunoassays

Abstract: Fluorescence immunoassays (FIA) have strong potential in enabling rapid quantitative immunological testing at point of care. Existing state of the art instruments employ laser scanning of FIA test kits, which require the use of electromechanical systems, making the instrument bulky, heavy and less reliable in the long term. There is a growing need for an extremely compact and reliable, motion-free, automated reader for accurate quantification of immunoassays. Here, we present ImQuant, an image based FIA reader… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In 2012, Mudanyali et al, demonstrated a cellphone-based rapid-diagnostic-test (RDT) reader platform that works with various lateral flow immuno-chromatographic assays and similar tests to sense the presence of a target analyte in a sample [ 16 ]. In 2015 and 2016, Chowdhury et al, developed a reader for quantitative lateral flow immunoassays using a line laser diode module to illuminate a lateral flow immunoassay test strip with fluorescent dye [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, Mudanyali et al, demonstrated a cellphone-based rapid-diagnostic-test (RDT) reader platform that works with various lateral flow immuno-chromatographic assays and similar tests to sense the presence of a target analyte in a sample [ 16 ]. In 2015 and 2016, Chowdhury et al, developed a reader for quantitative lateral flow immunoassays using a line laser diode module to illuminate a lateral flow immunoassay test strip with fluorescent dye [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to meet current clinical requirements, quantitative detection of targeted specimens has become necessary, and the development of rapid tests and image detection equipment has thus gained broad interest. Image-based immunochromatographic test strip readers have already been demonstrated by a few researchers [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%